(untitled) - Edmonds, W. Alex (Los Angeles, 2017)
This book covers the most practical and common research designs currently used in educational and the social and behavioural sciences. It will improve readers? ability to conceptualize, construct, test, problem solve and acquire knowledge, all of which are characteristics of scientific inquiry and the creative process required when conducting research.
Keywords: Giáo dục,Education; Nghiên cứu,Phương pháp luận,Research,Methodology